Genetic diversity analysis of chrysanthemum (Chrysanthemum grandiflorum) cultivars using RAPD markers - KUMAR, GUNJEET; SINGH, KANWAR PAL; PRASAD, K V; RANA, M K; NAMITA, NAMITA; PANWAR, SAPNA (The Indian Journal of Agricultural Sciences, 2014)
Identification and characterization of new cultivars is essential to meet DUS testing, address IPR issues and their utilization and conservation. Traditionally, morphological markers were used for germplasm characterization as being simple and irreplaceable. A total of 57 RAPD primers were screened and out of these 22 primers which gave sufficient amplification were selected for the study. Out of 207 bands generated, 175 were polymorphic with a polymorphism percentage of 84.54%. The polymorphism percentage ranged between 60% (OPA04) to 100% (OPA17, OPB-06, OPX14, OPX-19). The primer OPA08 generated least numbers of bands (4) and OPA06 generated maximum number of bands (17). The Rp values ranged between 0.82 to 8.18 for RAPD primers OPY-4 and OPX16, respectively with a mean value of 3.94 and the correlation between Rp and number of cultivars identified by each primer was fairly high (0.96). The primers OPX16, OPY6 and OPA04 distinguished higher number of cultivars of 49, 46 and 37 respectively. The UPGMA dendrogram indicated that the cultivars Maghi Orange and Maghi Yellow were sharing the maximum similarity (89%) and were close to Maghi White at a similarity level of 86%. The other cultivars sharing higher similarity levels were Flirt with Yellow Gold, Pink Cloud with Korean Small and Sadbhawna with Jubilee. RAPD proved to be useful for the characterization of the genotypes for their efficient utilization, management and IPR protection.